(untitled) (Journal of Recent Advances in Applied Sciences (pISSN 0970-1990), 2026)
Introduction: Leukemia comprises a heterogeneous group of hematological malignancies with varying clinical and epidemiological patterns across different regions. Understanding the local distribution of leukemia subtypes is important for improving early diagnosis, treatment strategies, and patient management. Aim & Objectives: This study aimed to evaluate the spectrum of leukemia and analyze its distribution according to age and gender in a tertiary care center in Northern India. Material & Methods: A retrospective observational study was conducted on 108 diagnosed cases of leukemia. Diagnosis was established using hematological, morphological, and cytochemical evaluation. Demographic and clinical details, including age, gender, and leukemia subtype, were collected from hospital records and analyzed statistically using the Chi-square test, with p < 0.05 considered statistically significant. Results: Chronic leukemias accounted for most cases (86.11%), with Chronic Myeloid Leukemia being the predominant subtype (75.92%), followed by Chronic Lymphocytic Leukemia (10.18%). Among acute leukemias, Acute Lymphoblastic Leukemia (9.25%) was slightly more common than Acute Myeloid Leukemia (4.62%). A mild male predominance was observed (M: F = 1.28:1), although no significant association was found between gender and leukemia subtype (p = 0.900). Age-wise distribution showed a significant association with leukemia subtype (p < 0.001), with ALL predominating in children, CML in middle-aged adults, and CLL in elderly individuals. Conclusion: Chronic leukemias, particularly CML, were the most common leukemias observed in this region, with distinct age-related patterns across different subtypes.